2017
DOI: 10.1007/s11430-016-8315-5
|View full text |Cite
|
Sign up to set email alerts
|

Genesis of the 2014–2016 El Niño events

Abstract: The 2015/2016 El Niño was one of the strongest El Niño events in history, and this strong event was preceded by a weak El Niño in 2014. This study systematically analyzed the dynamical processes responsible for the genesis of these events. It was found that the weak 2014 El Niño had two warming phases, the spring-summer warming was produced by zonal advection and downwelling Kelvin waves driven by westerly wind bursts (WWBs), and the autumn-winter warming was produced by meridional advection, surface heating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 59 publications
(71 reference statements)
0
32
1
2
Order By: Relevance
“…As a result, a pronounced reduction in precipitation rates was observed during Austral summer until the end of 2015 (Nobre et al, ). One reason for this extended drought was the occurrence of a very strong ENSO event between March 2014 and March 2016, according to the Multivariate ENSO Index (Hu & Fedorov, ; Lian, Chen, & Tang, ; Sánchez‐Murillo et al, ; Wolter & Timlin, ; Figure d).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, a pronounced reduction in precipitation rates was observed during Austral summer until the end of 2015 (Nobre et al, ). One reason for this extended drought was the occurrence of a very strong ENSO event between March 2014 and March 2016, according to the Multivariate ENSO Index (Hu & Fedorov, ; Lian, Chen, & Tang, ; Sánchez‐Murillo et al, ; Wolter & Timlin, ; Figure d).…”
Section: Discussionmentioning
confidence: 99%
“…There is a weak peak around April in the WP region. Recent studies suggest that WWBs in the WP occurring in later spring and boreal summer play an important role in maintaining the El Niño (McPhaden 1999;Menkes et al 2014;Chen et al 2015;Xue and Kumar 2016;Lian et al 2017). It's clear that CAM4 successfully captures the seasonality of the WWB occurrence over these two regions.…”
Section: Seasonal and Interannual Variabilities Of Wwbsmentioning
confidence: 99%
“…For example, it's not clear whether the modeled WWBs exhibit a stronger phase locking characteristic in boreal winter when more WWBs occur (Harrison and Vecchi 1997). It has not be examined yet whether the WWBs in late boreal spring and summer seasons over the central equatorial Pacific, which is important for triggering and maintaining the strong El Niño (McPhaden 1999;Menkes et al 2014;Chen et al 2015;Xue and Kumar 2016;Hu and Fedorov 2016;Lian et al 2017), can be correctly simulated in the coupled model. It's also not clear whether the spatial pattern of WWBs is realistically reproduced in the state-of-the-art models.…”
Section: Introductionmentioning
confidence: 99%
“…Significant distinctness and complexity has been observed in this event in terms of its fundamental characteristics and mechanisms of oceanatmosphere coupling system, compared with the previous two super El Niño events (Lian et al, 2017;Qi et al, 2017;. It is not enough to give a comprehensive interpretation for this super event by exclusively using conventional linear ENSO dynamical theories, implying that the nonlinear processes of ocean-atmosphere system may be responsible for these distinctness and complexities.…”
Section: Enlightenments and Thinkingmentioning
confidence: 84%
“…The comparison of dynamical mechanisms between these two stages showed that the amount of westerly wind bursts (WWBs) in the western tropical Pacific might be the main reason of the significant differences in the warming intensity during the two stages. In addition, the diagnosis based on an ocean reanalysis dataset showed that the eastward transport of surface oceanic heat in the equatorial central Pacific and the vertical heat transport in the equatorial eastern Pacific also directly contributed to the formation of this super event (Lian et al, 2017).…”
Section: The Distinct Characteristics Of the 2014-2016 Super El Niño mentioning
confidence: 99%